HUBUNGAN ANTARA KADAR HEMOGLOBIN DENGAN KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Avi Syifa (FKU 16 UMY 016, 2016)
Background: Chronic kidney disease (CKD) is a progressive decline in renal function is characterized by a decrease in glomerular filtration rate and increased blood creatinine levels requiring renal replacement therapy were fixed, in the form of dialysis or a kidney transplant. Deficiency of eritropoitin is one cause of anemia in CKD is characterized by a decrease in hemoglobin concentration. Decrease in hemoglobin levels is one of the factors causing the declining quality of life in patients with chronic kidney disease. Purpose: To determine the correlation between hemoglobin levels and quality of life in chronic kidney disease’s patients on hemodialysis in PKU Muhammadiyah Yogyakarta Hospital. Methods: This study’s design was observational analytic method with cross sectional approach. The subjects were 60 patients with chronic kidney disease on hemodialysis in PKU Muhammadiyah Yogyakarta Hospital from August 2015 through November 2015. Quality of life was measured by using a questionnaire from WHOQoL-BREF and Hb-level’s data obtained from medical records of patients. Analysis of the correlation using Kolmogorov-Smirnov test. Result: The result of the statistical analysis test correlation between hemoglobin-levels and quality of life in patients with chronic kidney disease on hemodialysis in PKU Muhammadiyah Yogyakarta with Kolmogorov-Smirnov test resulted in p = 0,740, where the value of p > 0,05 indicates that the correlation between the two variables are not significant statistically. Conclusion: There is no significant correlation between hemoglobin levels and quality of life in patients with CKD on hemodialysis in PKU Muhammadiyah Yogyakarta Hospital